2021
DOI: 10.3389/fonc.2021.773535
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic-Free Liver Transplantation Reduces the Recurrence of Hepatocellular Carcinoma After Liver Transplantation

Abstract: Ischemia reperfusion injury (IRI) is an adverse factor for hepatocellular carcinoma (HCC) recurrence after liver transplantation. Ischemic-free liver transplantation (IFLT) is a novel transplant procedure that can largely reduce or even prevent IRI, but the clinical relevance of IFLT and the recurrence of HCC after liver transplantation are still unknown. This retrospective study compared survival outcomes, HCC recurrence, perioperative data and IRI severity following liver transplantation (LT). 30 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Its application is able to procure, preserve, and implant liver grafts from DBD donors without stopping the blood and oxygen supply, thus entirely preventing hepatic IRI ( 26 ). A recent propensity-matched cohort study showed that IFLT recipients had a higher RFS rate at 1 and 3 years (92.2% and 86.7%) than conventional LT recipients (88.1% and 53.6%), with much lower liver damage ( 27 ). Though the oncological benefit of IFLT needs further observation and validation in a larger sample, this technique shows enormous potential not only for completely avoiding IRI but also for preventing associated HCC recurrence.…”
Section: Inflammation-targeting Cancer Therapy: Hit Two Birds With On...mentioning
confidence: 99%
“…Its application is able to procure, preserve, and implant liver grafts from DBD donors without stopping the blood and oxygen supply, thus entirely preventing hepatic IRI ( 26 ). A recent propensity-matched cohort study showed that IFLT recipients had a higher RFS rate at 1 and 3 years (92.2% and 86.7%) than conventional LT recipients (88.1% and 53.6%), with much lower liver damage ( 27 ). Though the oncological benefit of IFLT needs further observation and validation in a larger sample, this technique shows enormous potential not only for completely avoiding IRI but also for preventing associated HCC recurrence.…”
Section: Inflammation-targeting Cancer Therapy: Hit Two Birds With On...mentioning
confidence: 99%
“…Interestingly, one study demonstrated the protective effect of IFOT in recipients with HCC. Lower recurrence rates were seen through an IRI reduction [ 137 ]. In this propensity score matched analysis, the authors illustrated a better recurrence-free survival after IFOT (HR 3.728, 95% CI 1.172–11.861, p = 0.026), when compared to SCS alone [ 137 ].…”
Section: The Impact Of Machine Liver Perfusion On Tumor Recurrencementioning
confidence: 99%
“…Lower recurrence rates were seen through an IRI reduction [ 137 ]. In this propensity score matched analysis, the authors illustrated a better recurrence-free survival after IFOT (HR 3.728, 95% CI 1.172–11.861, p = 0.026), when compared to SCS alone [ 137 ]. The authors showed recurrence-free survival rates at 1 and 3 years after LT in recipients with HCC in the IFOT group of 92% and 87%, respectively, which were significantly higher than those (73.0% and 46.3%) seen in the cold storage group [ 137 ].…”
Section: The Impact Of Machine Liver Perfusion On Tumor Recurrencementioning
confidence: 99%
See 2 more Smart Citations